A fast handover scheme based on multiple mobile router cooperation for a train-based mobile network. (11th August 2010) - Huang, Zhiwu; Yang, Yingze; Hu, Huosheng; Lin, Kuo-Chi
True broadband access for high-speed train passengers has become a new trend in the world. To support the newly emerged mobile applications effectively, the mobile network's handover latency and packet losses during handover need to be as small as possible. To address this issue, a fast handover scheme based on multiple mobile router cooperation for mobile networks is proposed in this paper. Its basic idea is to take advantage of the features of the fixed line and routing information in the railway passenger transportation system in order to configure the mobile router's next care-of-address (CoA) in advance, thus reducing the new CoA configuration time. Moreover, two or more mobile routers spatially separated by a certain distance are configured on the railway train that enables different mobile routers to access different subnets during handover and cooperatively receive packets from each other. The overlapped reception of packets from deferent subnets makes the packet loss independent of the handover latency, and reduces packet losses during handover. The mathematical analysis and simulation experiments are presented to show the feasibility and effectiveness of the proposed scheme.